Epidemiological transition and distribution of stroke incidence in Tianjin, China, 1988–2010. (February 2016) - Jiang, G.; Li, W.; Wang, D.; Shen, C.; Ji, Y.; Zheng, W.
Abstract: Objectives: To examine the trends in epidemiological transition of stroke over the last two decades in Tianjin, and investigate the subtypes of stroke. Study design: A population-based epidemiological study using data from the Stroke Incidence Surveillance System of the Tianjin Centres for Disease Control and Prevention from 1988 to 2010. Methods: Almost 500, 000 cases were analysed to examine changes in the incidence of stroke between 1988 and 2010 by age, sex, subtype, year and urban/rural status. Results: The incidence of stroke amongst males increased from 136.8/100, 000 in 1988 to 387.0/100, 000 in 2010, and the incidence amongst females increased from 65.9/100, 000 in 1988 to 249.7/100, 000 in 2010. Over the study period, the proportion of haemorrhagic strokes decreased and the proportion of ischaemic strokes increased sharply in both men and woman; the differences were significant. Conclusion: The distribution of stroke subtypes changed dramatically over the study period. Changes in trend and subtypes of stroke have raised new challenges and there is a need for adjustment for stroke prevention in Tianjin. Highlights: The hemorrhagic stroke decreased. The cerebral infarction sharply increased in both men and woman significantly. The cerebrovascular disease is a major cause of death in Tianjin, ranking No. 2 after heart diseases. The incidence of stroke is still on the increase, particularly among the middle-aged and young people.